KEMAMPUAN EKSTRAK ETANOL DAUN JERUK PURUT (Citrus hystrix D.) UNTUK MENGHAMBAT BAKTERI Escherichia coli DAN Salmonella sp. PADA SUSU SEGAR - Yustina Wuri Wulandari; Kharis Triyono; Nanik Suhartatik; Mita Krisna Murti (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Kaffir lime leaves are often used as a flavoring. In addition to being used as a flavoring, kaffir lime leaves are known to be used as antimicrobials. Fresh milk has a high nutritional value, so good for the growth of pathogenic microbes. Therefore, treatment is needed on fresh milk by adding of kaffir lime leaves ethanol extract which containing active compounds to inhibit the growth of pathogenic microbes. The purpose of this research is to know the ability of kaffir lime leaves ethanol extract to inhibit E. coli and Salmonella sp. on fresh milk. This research uses explorative method with 2 factors. The first factor was concentration of kaffir lime leaves ethanol extract (20, 10, 5, and 2,5 g/ml), while the second factor was incubation time (0, 1, 2, and 3 hours). Analysis of this research include Total Plate Count (TPC) and calculation of count of E. coli and Salmonella sp. The results showed that the kaffir lime leaves ethanol extract able to inhibit the growth of E. coli and Salmonella sp. in fresh milk. Growth of E. coli and Salmonella sp. decreased significantly with increasing concentrations of kaffir lime leaves ethanol extract and incubation time.